Feasibility study in real-time teledentistry in Residential Aged Care Facilities - Dr Candy Fung; Dr Claudia Lopez Silva; Dr Diep Ha; Prof Laurence Walsh; Dr Matthew Nangle (Elsevier, 2023)
Aim or Purpose: This study aimed to assess the feasibility and validity of real-time teledentistry to address the unmet oral health needs of Priority Population 4 (National Oral Health Plan 2015-2024), residents in Residential Aged Care Facilities (RACFs). Materials and Methods: This feasibility study assessed oral health of residents and staff at two Queensland RACFs (March 2022-April 2023). Sixteen residents (mean age 79.3±8.68 years, 56% female & 44% male), and eight staff (mean age 33.3±6.16 years, 62.5% female & 37.5% male) participated. RBWH (HREC/2021/QRBW/77399) and UQ (2022/ HE000091) Ethics Committees granted approval for this study. Examination through real-time teledentistry using an intra-oral camera by RACF staff guided by a qualified dentist was compared to face-to-face clinical examination (one month later) by the same dentist using the Oral Health Assessment Tool (OHAT). Feasibility was assessed qualitatively through questionnaire on participants' experience on teledentistry. Validity was assessed through Bland-Altman analysis to determine the agreement in OHAT scored through the two methods. Results: The participantsfound that real time teledentistry was user-friendly in a RACF setting. Overall mean OHAT total score obtained through teledentistry was 4.13 (SD 3.11; 95% CI: 2.81 - 5.44), and examination was 3.88 (SD 3.05; 95% CI: 2.59 - 5.16). Bland-Altman agreement analysis showed no consistent bias between the two methods (-0.208; 95% CI: -3.68 to 3.26). Conclusions: The study demonstrated that real-time teledentistry is feasible and comparable to face-to-face examination to assess oral health in RACF. Therefore, teledentistry may be deployed to provide continuity of oral health assessment in RACF, thus reducing barrier to oral health care in this vulnerable population.